Feminist thought(s) as dirty intellectuality: the case of Andrea Dworkin - Pivec, Nataša (My University, 2015)
The wide spectrum of feminist thoughts, from art to epistemology, which are centred around gender and its multi-leveled arrangements in society is, when not aligned with predominant epistemic premises or artistic standards of hegemonic masculinity, rendered as Other or dirty. The concept of Otherness is ascribed to the knower/producer on behalf of her sex and her epistemic focus, which transgresses several dichotomous frameworks of the body–mind dualism, epistemological traditions, gendered categorization of professions, gender binarism and body norms of conventional femininity. The life and work of radical feminist Andrea Dworkin was analyzed in order to confirm the theoretical premise of the article, namely that when a woman positions herself as a knower and produces knowledge, (self)categorized as a feminist, she is perceived as a threat to the system of structures, discourses and practices of the gender order.
Keywords: Andrea Dworkin; embodiment; feminism; Feminismus; knowledge; Other; Wissen; ddc:300